Priests and preachers entering Islam [videorecording] - Sheikh Yusuf Estes; One Islam Production; Saba Islamic Media; ICRA Youth Centre, Inc. ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
A talk by Sheikh Yusuf Estes on the story of how he found Islam. Sheikh Yusuf Estes embraced Islam at the age of 50 after meeting with a muslim for the first time in his life. He was a priest and Christian musician minister as well as owner of several music stores
Title from title screen
Speaker: Sheikh Yusuf Estes
Keywords: Sheikh Yusuf Estes; Muslim converts -- United States -- Texas; Islam